Federated learning with Python : design and deploy powerful federated learning applications on private data using PySyft, TFF, STADLE /: design and deploy powerful federated learning applications on private data using PySyft, TFF, STADLE. (2022) - Nakayama, Kiyoshi; Jeno, George
No abstract available